CRYPTOCURRENCY PRICE VOLATILITY ANALYSIS ON BITCOIN AND ALTCOINS BEFORE AND DURING THE COVID-19 PANDEMIC IN INDONESIA - Wulandari, Hanum Dyah; Rahman, Ilyasin Aditya (Journal of International Conference Proceedings, 2022)
The emergence of COVID-19 in December 2019 in China, until it spread to Indonesia in early March 2020 was designated as the center of the transmission of COVID-19. It negatively impacted the financial sector and caused cryptocurrency volatility to increase significantly. Therefore, the purpose of this study is essential to determine the volatility of cryptocurrencies and the method of estimating the price of cryptocurrencies. This shows that cryptocurrency fluctuations are unstable and irregular compared to equities, so the cryptocurrency market is more risky and difficult to predict during the COVID-19 pandemic. In this study, the analytical tools were quantitative and descriptive using the ARIMA and GARCH time series models for time series forecasting. The secondary data were used to determine the existence of volatility. Thus, ARCH Effect is the best model to estimate the volatility price of a cryptocurrency. As a result of forecasting, both bitcoin and altcoins tend to the uptrend.